2009
DOI: 10.1038/nchembio.157
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-directed tosyl chemistry for protein labeling in vivo

Abstract: Here we describe a method for the site-selective attachment of synthetic molecules into specific 'endogenous' proteins in vivo using ligand-directed tosyl (LDT) chemistry. This approach was applied not only for chemically labeling proteins in living cells, tissues and mice but also for constructing a biosensor directly inside cells without genetic engineering. These data establish LDT chemistry as a new tool for the study and manipulation of biological systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
288
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(293 citation statements)
references
References 25 publications
4
288
0
1
Order By: Relevance
“…Whereas all previously discussed protein tags rely on genetic manipulations, namely the expression of the POI as fusion to the particular protein tag, Tsukiji et al reported a native protein labeling strategy [29]. In this method, the ligand binds with high affinity to the native target protein directing a reactive group to the surface of the protein that forms a covalent bond through proximity-induced reactivity.…”
Section: Proximity Induced Covalent Protein Tagsmentioning
confidence: 99%
“…Whereas all previously discussed protein tags rely on genetic manipulations, namely the expression of the POI as fusion to the particular protein tag, Tsukiji et al reported a native protein labeling strategy [29]. In this method, the ligand binds with high affinity to the native target protein directing a reactive group to the surface of the protein that forms a covalent bond through proximity-induced reactivity.…”
Section: Proximity Induced Covalent Protein Tagsmentioning
confidence: 99%
“…By using a ligand-directed, S N 2 reactive, tosyl group bound to the probe of interest, the ligand is released on conjugation and so does not compromise protein function 193 . The amino acids modified by this technique include non-traditional nucleophilic amino acids such as histidine and glutamic acid, strongly suggesting this as a reaction driven by proximity, rather than nucleophilicity 194 .…”
Section: Box 2 | Comparing Strategies For Positional Controlmentioning
confidence: 99%
“…The molecule mediating the interaction is released when the covalent coupling of the label to the protein takes place, which reduces its impact on protein function compared to previous approaches. This method has been shown to allow selective native protein labeling in the cell interior and even in blood cells of living animals [73 ]. The method is remarkably specific, but the general reactivity of the tosyl group with nucleophiles may inherently limit the attainable selectivity towards proteins of low abundance.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…A less invasive route has been described by Hamachi and co-workers and is based -similar to their self-labeling tag approach (see above) -on turning an initially noncovalent interaction into a covalent one. Here, the noncovalent interaction is provided by a molecule that specifically binds to the native protein of interest, for example, an enzyme inhibitor [73 ]. The reactive group used is the tosyl group, which is why this approach has been termed liganddirected tosyl chemistry (LDT).…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%